2007
DOI: 10.1159/000098576
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Topically Applied Indigo Naturalis Ointment in Patients with Plaque-Type Psoriasis

Abstract: Background: It has been reported in the Chinese literature that indigo naturalis exhibits potential antipsoriatic effects in systemic therapy. Objective: To evaluate the efficacy and safety of topically applied indigo naturalis on treating plaque-type psoriasis and to analyze the histological change in skin tissues. Methods: Fourteen patients with chronic plaque psoriasis were enrolled. The patients were topically applied with either indigo naturalis ointment or vehicle ointment on contralateral skin lesions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 18 publications
1
80
0
Order By: Relevance
“…Topical and oral Qing-Dai are used to treat various inflammatory diseases and dermatosis, such as psoriasis [16][17][18] . Traditionally, Qing-Dai has been used in Chinese medicine to treat UC patients; however, published data on the safety and efficacy of Qing-Dai for UC patients are lacking in the English literature.…”
Section: Clinical Efficacy and Safety Of Oral Qing-dai In Patients Withmentioning
confidence: 99%
“…Topical and oral Qing-Dai are used to treat various inflammatory diseases and dermatosis, such as psoriasis [16][17][18] . Traditionally, Qing-Dai has been used in Chinese medicine to treat UC patients; however, published data on the safety and efficacy of Qing-Dai for UC patients are lacking in the English literature.…”
Section: Clinical Efficacy and Safety Of Oral Qing-dai In Patients Withmentioning
confidence: 99%
“…The patients' blood parameters as well as liver and renal function tests were within the normal range. The same authors' molecular study revealed decreased expressions of Ki-67 proliferating marker as well as CD3 inflammatory marker, whereas filaggrin, the differentiation marker, was increased in the epidermis [11].…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 87%
“…Its major active components are indirubin, indigo, and tryptanthrin. According to the literature reports, Indigo naturalis exhibits antiviral, antibacterial and anti-tumor properties [9,11]. TCM uses this herb in the treatment of various inflammatory and infectious diseases e.g.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 8 years, we have treated more than 10,000 patients with skin psoriasis using indigo naturalis, and our previous clinical trial results attracted much attention from mainstream newspapers and magazines. Our evidence-based research results showed that topical application of indigo naturalis ointment can significantly improve psoriatic symptoms [2,3]. …”
Section: Introductionmentioning
confidence: 99%